THE FACTORS RELATED TO THE INCIDENT OF IKTERUS IN NEWBORN BABIES AT RSKDIA PERTIWI, MAKASSAR - ruth ruth (Stikes Graha Edukasi Makassar, 2019)
Introduction : Ikterus occurs when there is bililirubin in blood. In the majority of the newborn babies the ikterus will be found in the fist week of the babies' life. It is reported that Ikterus incident are founf in 60% of the babies born in complete months, and in 80% of babies born less than the complete months. Method: The research used the observational method with the approach of the Cross Sectional Study. The research is conducted in November 2017. The population includes all nifas mothers present at RSKDIS Pertiwi, Makassar in 2017. The samples are chosen using the Accidental Sampling Technique. Result : The research result indicates that there is a correlation between the adequate amount of breast milk for the babies and the incident of Ikterus in newborn babies. The research result also reveals that there is a correlation between the gestation age of the post-partum mothers and the incident of Ikterus in the newborn babies. Finally, the research result indicates that there is a correlation between the delivery type and the incident of Ikterus in the newborn babies. Conclusion : There is a correlation between the adequate amount of breast milk in newborn babies, between the gestation age and the age of the post partum mothers and between the delivery type and the incident of Ikterus in newborn babies. Thus, it is suggested that the midwives in implementing the midwifery care, particularly in the pathology of Ikterus cases, should collaborate/consul the doctors as the early step to prevent the increasing development of bilirubin so that the Ikterus incident does no happen.